THE RELATIONSHIP of SMOKING HABITS AND THE USE of MOSQUITO MEDICINE WITH THE EVENT of ARI in TODDLERS (Case Study in Bulurejo Village, Benjeng District, Gresik Regency in 2021) - Putri Firda Wahyuni Putri; Suprijanani; Setiawan (Jurnal Hygiene Sanitasi, 2021)
Acute Respiratory Infection (ARI) is a disease that is often found in children under 5 years of age. Gresik Regency was ranked third out of 38 regencies/cities in East Java Province in finding pneumonia sufferers. Behavioral factors are one of the causes of respiratory diseases, one of which is ARI. This study aims to analyze the relationship between family members behavior and the incidence of ARI in toddlers in Bulurejo Village, Benjeng District, Gresik Regency in 2021.The research method used is correlational analytic method with case control approach with a total sample of 23 people. Determination of case and control samples were taken with a proportion of 1: 1, namely 46 people. Data collection techniques are primary data collection through questionnaires and analyzed using Chi Square test.This study used univariate and bivariate analysis. The results showed that there was a relationship between the smoking behavior of family members with the incidence of ARI in toddlers with p value 0.006 and there was no relationship between the behavior of using mosquito coils with the incidence of ARI in toddlers with p value 0.070.The conclusion from the results of the study there is a relationship between the behavior of family members with the incidence of ARI in toddlers. It is hoped that the puskesmas institution will always provide education or counseling to the community, especially parents who have toddlers not to smoke in the house or close to their children.